Analisis SWOT Peran Strategis Perpustakaan Sekolah Al-Ittihad Pekanbaru dalam Meningkatkan Pelayanan Prima - Latiar, Hadira; Siddik, Muhammad Nur Fakhri; Nadiva Salsabila, Siti (Jurnal Tadwin, 2024)
The library has a strategic role in supporting learning and research at Al-Ittihad School. SWOT analysis is carried out to identify strengths, weaknesses, opportunities and challenges. In terms of deficiencies, libraries face the problem of dust on bookshelves, lack of preservation, limited warehouse space, shortage of librarians. However, libraries have advantages such as attractive interior designs, comfortable rooms, and facilities such as sofa chairs, study tables, computers, and well-maintained book collections. The presence of CCTV, lockers, good bookkeeping and textbooks are an added value. The SWOT analysis identified development opportunities, including interior design appeal, expansion of computer use, and potential for community events.  The challenges required thoughtful solutions, including regular cleaning, preservation programs, optimization of warehouse space, additional librarian training, investment in refrigeration systems, and installation of security systems. The research method used was qualitative by conducting observations and SWOT analysis at the Al-Ittihad School Library. The library's strengths involve the use of the SLiMS application, availability of WiFi, and appropriately skilled staff. Limited budget for updating collections is one of the weaknesses, even though the level of student and teacher visits has increased. The development plan involves utilizing the latest technology, partnerships with publishers, and support for online learning. Threats come from digital platforms which can threaten the attractiveness of libraries, so libraries need to maintain their existence by creating a comfortable environment. This research aims to provide a comprehensive picture of library conditions and support better strategic planning. By understanding SWOT, libraries can identify priorities, overcome weaknesses, and optimize potential to provide better services to the community